A study of the roles of colour and shape in the perception of perfume - Chan, Wei Wen (2015)
Much research has been done on the effects of colour on bottles ( Eysenck, 1941; Docus, 1932; Byrnes, 1983 etc.). It has been noted, however, that none of these studies address the issue as to how colour, together with the shape of the perfume container affect the perception of perfume. This phenomenon is important as consumers' perception of a product is the result of an interaction of various attributes associated with the product. For instance, the perception of the perfume is usually the result of the fragrance used (olfactory), packaging (colour and shape) and the advertising content and context employed. Although consumers appear to judge perfumes by their scent, it is not known how the colour and shape of the perfume bottle affect their perception of perfume. This exploratory research therefore aims to examine the effect of colours and shapes used in perfume packaging on the perception of fragrance. An experiment was conducted using undergraduates as respondents. The colour stimuli (bright, dark and pastel) and shape stimuli (classical, contemporary and conventional) were given to all respondents. A full 3 x 3 factorial design was adopted. The data collected was factor analysed and ANOVA tests were performed to analyse colour and shape effects on the perception of perfume. The results revealed that different colours and shapes elicited different perceptions of perfume. In addition, there were highly significant interaction effects between colours and shapes of bottles. The most preferred combination is bright and contemporary shaped bottle. Implications for the findings and suggestions for future research will also be discussed.